Levantamento de crianças com indicadores de altas habilidades em Jaboticabal/São Paulo - Marques, Clayton dos Reis (2010)
Few people with High Abilities/Giftedness are identified in Brazil, and fewer are those that receive satisfactory service to develop their full potential. The field needs more production of knowledge, mainly focusing on local realities, and a greater dialogue between the different theoretical lines. This research represents a small step in that direction. The overall objective of the study was to identify, register and analyze quantitatively the number of students with indicators of High Abilities/Giftedness identified by their teachers on a representative sample of the population of Jaboticabal city, São Paulo State, Brasil. Teachers of second, third and fourth grades from elementary education were invited to participate in the research. The study had characteristics of an exploratory study, in terms of a quantitative survey study, to provide an overview of a specific event or phenomenon. Data analysis aimed to identify variables in the natural environment. Seventy six teachers of public schools participated in the survey and this number represented 81% of the participants. Three instruments were used to collect data: an identification form, a characterization form and an indicator form for High Abilities/Giftedness indentification. The results indicated the presence of children with indicators of High Abilities/Giftedness in the surveyed classrooms, 38% of the children had one or more indicators. The number of children with indicators of High Abilities/Giftedness was 809 children among 2148 observed by teachers. The number of indicators observed (2760) were consistent with the reviewed literature about the topic and the teachers proved to be able to identify it.